Antipsychotic drugs and QT interval prolongation - Novak Šarotar, Brigita (Anali PAZU, 2022)
Prolongation of myocardial repolarization, i.e. lengthening of the QTc interval on surface electrocardiogram (ECG), with increased risk of cardiac arrhythmias, has been recognized as a side effect of many drugs. Most first and second generation antipsychotic drugs can cause dose-related prolongation of QTc, although there are important differences in the potency of individual agents. ECGs in 46 patients suffering from schizophrenic disorder and treated with different antipsychotic drugs one week after the admission to the psychiatric hospital were analyzed in this prospective observational study. Hearth rate, QT interval and QTc interval were assessed. The average daily dose of prescribed antipsychotic drugs was calculated.  Average QTc interval was 417 msec, only 3 out of 46 (6,5%) patients had QTc over 450 msec and only one patient (2,2%) had QTc over 500 msec. No differences in QTc interval between patients who were treated either with first or second generation antipsychotic drug or with combination of both were found. Female participants had significantly longer OTc interval than male participants (p
Keywords: schizophrenia; treatment; antipsychotic drugs; QT prolongation